Denda dalam Pembiayaan Bai’ Bitsaman Ajil Menurut Perspektif Fiqh Muamalah - Achruh, Andi Athifah Amalia (SAFE-Network, 2023)
Bai' Bitsaman Ajil is a ba'I (sale and purchase) transaction in which the bank is the seller and the customer is the buyer. BBA is a sale and purchase transaction of services or goods where the original price is added to the profit submitted and the nominal is agreed between the buyer and the seller. This study aims to further discuss Fine in Financing Bai' Bitsaman Ajil according to the Fiqh Muamalah Perspective. This study uses descriptive qualitative methods to describe events (phenomena) or conditions of the observed object. The application of fines to BBA transactions can be carried out but with the aim of protecting the rights of financiers and according to the DSN-MUI fatwa Number 17/DSNMUI/IX/2000 concerning penalties in the form of fines for financing recipients who are able but delay or take time to fulfill their obligations.